Sosialisasi Inovasi Pangan sebagai Upaya Pencegahan Stunting dengan Pemanfaatan Tahu dan Jamur - Muhammad Dafa Ulhaq Bintoro; Anggita Nurlathifa; Mutiara Rahmi; Maghfira Cursiva; Meidya Ayu Prameswari; Gita Khonsa Rezkania; Azka Nurissyaban Achmad; Aditya Reyhan Prasetyo; Gilang Ardyansyah; Tukiman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Stunting is a serious health problem for toddlers in Indonesia. One of the main factors causing stunting is the lack of adequate nutritional intake during the first thousand days of life, which is a crucial period for a child's growth and development. This is due to the lack of public knowledge about nutritional intake since and after in the womb. Through the KKNT Bela Negara work program, it is hoped that it can provide knowledge about how to prevent and overcome stunting by fulfilling nutritional intake, especially protein, by providing food innovations with tofu and mushrooms as raw materials. The counseling was carried out in Lebo Village, Sidoarjo, East Java. The methods used include preparation and planning, program implementation, and innovation development. The results of this service are great enthusiasm from the counseling participants and increased knowledge about stunting and good nutritional intake, especially protein, to prevent and overcome stunting.